Assessment of cardiometabolic risk factors in various phenotypes of masked hypertension - B. I. Geltser; V. V. Orlova-Ilinskaya; O. O. Vetrova; V. N. Kotelnikov; R. S. Karpov (Кардиоваскулярная терапия и профилактика)
Aim. To assess the relationship of cardiometabolic risk factors in patients with various phenotypes of masked hypertension (MH).Material and methods. The study included 207 men with a median age of 34,6 years [32,3; 36,3] being systematically stressed. All examined patients had normal clinical blood pressure (BP), and there was no history of its increase. We conducted 24-hour ambulatory blood pressure monitoring (ABPM), carotid duplex scan with determination of the intima- media thickness (IMT). The levels of total cholesterol (TC), low (LDLC) and high-density lipoprotein cholesterol (HDL-C), triglycerides (TG) were determined. Body mass index, visceral adiposity index, lipid accumulation product index and waist-to-height ratio were calculated. We performed clustering of ABPM data, calculated the odds ratio of association between cardiometabolic risk factors and certain MH phenotypes.Results. MH was diagnosed in 142 (68,6%) patients examined, divided into 3 clusters: systolic-diastolic — SDMH (50,7%), isolated systolic — ISMH (27,5%) and isolated diastolic — IDMH (21,8%). Impaired lipid metabolism, visceral adiposity, IMT increase and atherosclerotic plaques were more often recorded in patients with SDMH and IDMH. The levels of TC, LDL-C and IMT were highest in individuals with IDMH. Odds ratio analysis indicated significant associations of SDMH and IDMH phenotypes with indicators of visceral adiposity, IMT, TG, TC, LDL-C and TG/HDL-Cl.Conclusion. Clustering of ABPM data in individuals with MH and comparing related phenotypes with cardiometabolic risk factors complements their clinical and functional characteristics and can be a useful tool for improving customized prevention and therapy programs.